Differential contribution of Yersinia enterocolitica virulence factors to evasion of microbicidal action of neutrophils. - Ruckdeschel, K (1996)
The differential contribution of the virulence factors invasin, protein tyrosine phosphatase (YopH), cytotoxin (YopE), and adhesin (YadA) of Yersinia enterocolitica to evasion of the antibacterial activities of polymorphonuclear leukocytes (PMNs) (oxidative burst, phagocytosis, killing) was analyzed. We constructed virulence gene knockout mutants and a novel two-plasmid system allowing production and secretion of individual virulence factors. Wild-type Y. enterocolitica WA-314 harboring the virulence plasmid pYV08 resisted phagocytosis and killing by PMNs. Moreover, strain WA-314 was able to inhibit the neutrophil oxidative burst upon stimulation with opsonized zymosan independently on preincubation with normal human serum or YadA-specific serum. These phenotypic properties of strain WA-314 were differentially affected when mutants impaired in YadA production or Yop secretion were used. A more detailed analysis revealed that YopH plays the dominant role in suppression of the antibacterial action of PMNs without damaging the cells. The YopH suppressing effect could be enhanced by coproduction of YopE and YadA. The contribution of YadA is attributed to the adhesin function promoting interaction with PMNs under both opsonizing and nonopsonizing conditions. In contrast, invasin seems to mediate only opsonin-independent interaction with PMNs. Taken together, our results demonstrate that YopH, YopE, and YadA act in concert towards neutrophil attack to enable extracellular survival of Y. enterocolitica in host tissue.